Current state of beech in the experimental plantations and arboretums in northeastern Ukraine and prospects of its use - Los, S. A.; Samoday, V. P.; Tereshchenko, L. I.; Birchenko, D. Ye. (Forestry and Forest Melioration, 2020)
Introduction Representatives of the genus Fagus are mainly forest-forming species of first storey of stands. European beech (Fagus sylvatica L.) outside its natural range is used to plant forest stands, mainly in western regions of Ukraine. On the right bank of the Dnipro, it forms productive stands (Korinko 2007, Belous 1962, Kokhno & Parkhomenko 2002). Despite the fact that the Left-Bank part of Ukraine has a more continental climate compared to the climate in the natural range of beech, the results of the European and Crimean (Fagus taurica Popl.) beeches introduction were positive in most of the cases (Ihnatenko et al. 2006, Los et al. 2014). According to previous studies, European and Crimean beeches in the northern Left-Bank Forest-Steppe have mainly high adaptive properties and are characterized by sufficiently high quantitative and qualitative indicators (Los et al. 2014, 2018). Thus, the introduction of these species can be considered relatively successful. The aim of the study was to determine how promising the species of the genus Fagus are for the plantations of different purposes in the northeast of Ukraine based on a complex assessment of the growth and development of Fagus trees in the experimental plantations and arboretums. Materials and Methods The article represents generalized results of the research of beech in arboretums and experimental plantations in the northeast of Ukraine, mainly in fresh fertile sites, on dark grey forest soil of loamy mechanical composition. The study has been carried out in recent years, in accordance with generally accepted forest mensuration and tree breeding methods, as well as by an improved methodology for a complex assessment of promising non-native tree species. Results In most of the plots (6 out of 9) the trees of different beech species were in good and satisfactory conditions, mass damage by pests or diseases had not been detected. The 56-year-old trees in the experimental plantation in Trostianets Forest Enterprise of Sumy Region had the highest growth intensity. The average annual growth by height was from 0.48 to 0.62 m there, and by diameter – from 0.48 to 0.66 cm. The part of trees of I and II selection categories were 23.1–24.0%. The studied plantations in Kharkiv Region had worse growth rates. A high proportion of multitrunk trees (50–79%) was observed in provenance test in the Kharkiv Forest Research Station. Comparison of the average heights and diameters of European beech climatypes in provenance test in Kharkiv Region (Ukrainian Research Institute of Forestry and Forest Melioration) showed the advantages of the variant originating from the Shchyrets district (Transcarpathia). A trunk volume of an average tree of this climatype at the age of 48 was twice as large as the other variants had and almost the same as that of the common oak. The growth intensity indicators of Crimean beech were similar to those of European beech. The increase in the height of Eastern beech in the arboretum of Kharkiv National Agrarian University was similar to that of forest beech at other sites in Kharkiv Region, but Eastern beech was characterized by the largest increase in diameter (0.7 cm/year). Regular fruiting and self-seeding of European and Crimean beeches were noted in both the experimental plantations and arboretums of Trostianets Forest Enterprise, Ukrainian Research Institute of Forestry and Forest Melioration and Kharkiv National Agrarian University. Most of the observed stands have been assessed as 4 or 5 degrees of acclimatization according to the scale of O. Lypa. The total score of the complex assessment of most beech objects on six indicators was from 13 to 28. The results of the assessment of two forest beech plantations (experimental crops and a site in the arboretum of Trostianets Forest Enterprise) showed that the species is promising for its usage in forestry. The findings indicate not only a high adaptive capacity of the genus Fagus species when being introduced, they also point at their high plasticity. Therefore, we can assume that these species are able to tolerate an increase in the climate’s continentally in their natural areas with no significant loss in productivity. However, this suggestion requires a further study. Conclusions European beech in the experimental plantations of Trostianets Forest Enterprise in Sumy Region showed better growth intensity and trunk quality compared to other studied Fagus trees there, so to English oak of a local origin (height was 13.5% higher, diameter was 6.4% higher). Growth intensity rates of Crimean beech were similar to those of European beech. In other plots of the experimental plantations and in arboretums, beech was characterized by growth indices equal or below the yield table level of English oak. In most of the observed stands regular fruiting and self-seeding were noted. According to the results of the complex assessment, both European and Crimean beeches are recommended to use when establishing forest plantations in the Forest-Steppe part of Sumy Region, as well as in landscaping in Kharkiv and Sumy Regions. 9 Figs., 3 Tables, 23 Refs. Key words: Fagus, complex assessment, multitrunk, selection category, reproduction.